Possible Gardens: cosmopolitical worlds - Bragança, Luciana Souza (Frontiers in Environmental Science, 2023)
This article presents some of the reflections produced by the Possible Gardens research, which explores the world of gardens where living beings interact directly, creating multispecific worlds. It is directed toward everyday gardens, which are still very present in Brazilian cities. It uses comparative case studies of multiple exemplar cases throughout the Arrudas River territory in the city of Belo Horizonte, Brazil. The aim is to present the contributions of the Possible Gardens, this expanded category of garden understood as cosmopolitical worlds, to the thinking of contemporary cities based on ecological practices derived from urban daily life. In addition, it opens an understanding of the potential of gardens as a culturally relevant element, as an example and catalyst for environmental policies.